Absorption spectra and chromonic phase in aqueous solution of perylenetetracarboxylic bisimides derivatives - Camorani, P.; Furier, M.; Kachkovskii, O.; Piryatinskiy, Yu.; Slominskii, Yu.; Nazarenko, V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
In this article we report the complex investigation of perylenetetracarboxylic bisimides derivatives in water solution. The results deal with all possible concentration in wide range of temperature. The experimentally observed of long wavelength maximums in absorption spectra with increasing of concentration can be attributed to decrease individual molecules of the dye and to the formation of aggregates. This fact is also responsible for the shift and form change of emission spectra.